2017
DOI: 10.20319/pijss.2017.32.746761
|View full text |Cite
|
Sign up to set email alerts
|

Linguistic Sexism in the Iranian High School Efl Textbooks

Abstract: As it is noted by the Iranian Ministry of Education

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Although this study showed improvement to some areas of the textbooks when compared with the results of the previous research which examined the same textbooks (1999 edition), there is still more room for improvement to provide an equal opportunity for learning for all students. As it was highlighted in Vahdatinejad & Bahiyah (2017), all EFL teachers have noticed linguistic sexism in the Iranian EFL school textbooks, therefore the findings of this study fortify teachers opinions that textbooks need to be revised in terms of gender equality.…”
Section: Discussionmentioning
confidence: 54%
“…Although this study showed improvement to some areas of the textbooks when compared with the results of the previous research which examined the same textbooks (1999 edition), there is still more room for improvement to provide an equal opportunity for learning for all students. As it was highlighted in Vahdatinejad & Bahiyah (2017), all EFL teachers have noticed linguistic sexism in the Iranian EFL school textbooks, therefore the findings of this study fortify teachers opinions that textbooks need to be revised in terms of gender equality.…”
Section: Discussionmentioning
confidence: 54%
“…On the top of that, Vahdatinejad examined linguistic sexism on the textbook. Later, the result revealed lack, unfair, and unbalance women exposure in the textbook (Vahdatinejad, 2017). Later, Fahrian, Alek and Wekke (2019) investigated gender representation in the EFL textbook used by Islamic school.…”
Section: Introductionmentioning
confidence: 99%